Pengelolaan Badan Usaha Milik Desa (BUMDes) Wisata Alam Sulili di Desa Baebunta Kecamatan Baebunta Kabupaten Luwu Utara - Herlinda, Rhesky; Dunakhir, Samirah; Idris, Hariany (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This study aims to analyze the implementation of the management system at BUMDes Wisata Alam Sulili in Baebunta Village, Baebunta District North Luwu Regency. The population in this study is BUMDes Wisata Alam Sulili and the sample in this study is the BUMDes administrators and managers who participate in managing BUMDes. The data collection techniques used in this study are observation, interviews, and documentation. The data analysis technique used in this study is Qualitative Descriptive. The results of this study indicate that the management process of the Village-Owned Enterprise (BUMDes) in Baebunta Village, starting from the Planning, Observation, Business Type Arrangement, Maintenance, and Results Report stages, has not been fully carried out based on the principles of BUMDes management according to Government Regulation Number 11 of 2021. Furthermore, the stage of reporting the results of BUMDes in Baebunta Village is not yet open or transparent to the community, so it is necessary to improve the aspect of financial accountability in managing its business units. For future researchers who will conduct research on the same topic, it is recommended to conduct a more in-depth study and add research variables so that the results can be compared with those found in previous studies.